Bats:: Neglected Agents of Sustainability (Sustainability in Debate, 2016)
When discussing sustainability, bats cannot be left out.These mammals have inhabited our Planet for more than52 million years11 and, during this period, they have evolvedinto an incredible amount of species exploring a greatvariety of food and shelters. There is currently a worldwidedistribution of 1,200 identified bat species. Amongmammals, bats are only outnumbered by rodents, whichaccount for a total of 2,500 species.